Sputtered NiOx Films for Stabilization of p+n‐InP Photoanodes for Solar‐Driven Water Oxidation. Issue 11 (18th March 2015) - Sun, Ke; Kuang, Yanjin; Verlage, Erik; Brunschwig, Bruce S.; Tu, Charles W.; Lewis, Nathan S.
<x xml:space="preserve">Abstract</x> A photoanode protection strategy using a multifunctional NiOx coating is presented. The transparency/antireflectivity, low electrochromism, conduction of holes, corrosion protection, and active electrocatalysis for water‐oxidation half‐reaction are described.